Beneath the bed and other scary stories - Brallier, Max; Rubegni, Letizia (New York, New York : Acorn/Scholastic Inc., 2019)
The kids at school dare John to visit the old house on the hill at night, and when he and his sister go in they find dusty dishes set on the table, a book open like it is waiting for a reader, and something hiding under the bed in the attic--and that is only one of the five scary stories with unexpected twists that are included in this collection.
Beneath the bed -- A hair down to her stomach -- The statue -- A dark and stormy night -- The noise at the window.
Publication, size and pagination may vary.
460
Keywords: Fear -- Juvenile fiction; Horror tales; Children's stories, American; Short stories; Horror stories; Short stories; Horror fiction